MOTIVATIONS OF RURAL TOURISM ACTORS PRESENTING LOCAL FOOD AS THEIR SPECIAL ATTRACTION IN SLEMAN REGENCY - Widiyanto, Dodi; Susanto, Ari; Pranata, Yoga; Rijanta, R. (ITB Journal Publisher, LPPM ITB, 2015)
Rural tourism is developing due to its unique attractions. One of attractions that can be found in rural tourism is local food. Local food are presented by meals and/or snacks. This paper aims to describe the motivations of rural tourism actors, its obstacles and prospects on how to offer local food in tourism villages. A qualitative approach is employed in this research. The data for this paper were collected from in-depth interview and field notes. There are various motivations why rural tourism actors presenting local food, such as environmentally-friendly, economy, diversification, shows the own products to the tourists, offers local food as an attraction to the tourists in order to show the local wisdom, cultural restoration, uniqueness, offers rural nuance, introducing cultural and rural lifestyle, and empowering surrounding areas. The obstacles on presenting local food in tourism villages: the availability of original ingredients of local food products, availability of the cookers, professionallism on preparing local food, willingness of the skillfull inhabitants to teach others how to produce local food, tourists appetizing, and tourism awareness. Finally, local food still have prospects to be developed in tourism villages with supported on the effort to solve jealousy, the spirit when they sell local food as their tourism village products, environmentally friendly practices, innovation, collaboration with other agencies, and cultural philosophy